Upaya Meningkatkan Motivasi Belajar Matematika Peserta Didik Kelas XI MIPA 2 Menggunakan Model Problem Based Learning Melalui Pendekatan Saintific dan TPACK - Reni Yanuarni (Journal on Education, 2021)
This study uses a Problem Based Learning model with an integrated scientific approach TPACK assisted by video learning media and Power point on matrix material to increase students' learning motivation. The subjects in this study were students of class XI MIPA 2 SMAN 15 Pekanbaru. The instruments used are observation sheets, questionnaires and tests. This research was carried out in two cycles, where each cycle consisted of two meetings and one cycle test, each cycle consisting of 4 main activities, namely planning, action, observation, and reflection. From the results of the study, it was found that there was an increase in students' learning motivation by using the Problem Based Learning model with an integrated scientific approach TPACK assisted by video learning media and Power point on matrix material. The results showed that the motivation of students has increased. This can be seen from the average value in the first cycle which is 97.79 in the medium category, increasing in the second cycle to 105.5 in the high category.